Determinants of Uganda’s Debt Sustainability: The Public Debt Dynamics Model in Perspective - Kijjambu, Frederick Nsambu; Musiita, Benjamin; Katarangi, Asaph Kaburura; Kahangane, Geoffrey; Akampwera, Sheilla (Journal of Economics and Behavioral Studies, 2023)
To investigate Uganda’s debt sustainability determinants. The fundamental framework for this study is the public debt dynamics model, which looks at connections between changes in public debt and important macroeconomic factors such as real GDP, primary balance, currency rate, real interest rate, and trade openness. While acknowledging the significance of the primary variables identified by Mupunga and Le Roux, our empirical analysis of a country’s debt dynamics extends beyond these factors. Additional considerations include the incorporation of controls such as the production gap and the non-interest current account balance. Tailored to Uganda’s economic context, our comprehensive empirical model aims to provide a nuanced understanding of the diverse determinants influencing debt dynamics in the region. The major conclusions indicate that the Primary Balance, Real Interest Rate, and Real Effective Exchange Rate all positively and significantly affect the debt ratio, suggesting that fiscal surplus, low-interest rates, and currency appreciation are favorable to debt reduction and sustainability. The paper also finds that the debt ratio is negatively and significantly influenced by the Current Account Balance, indicating that trade surplus is beneficial for debt management. The paper further finds that the debt ratio is not significantly influenced by GDP growth, suggesting that economic growth may not have a strong effect on debt dynamics in Uganda. Given the significant impact of the "Primary Balance" on the "Debt-to-GDP ratio in the long run, policymakers should prioritize maintaining a fiscal surplus and prudent fiscal management. Implementing measures to enhance revenue generation, control government expenditures, and reduce budget deficits can contribute to reducing the debt burden and ensuring long-term debt sustainability. To keep the debt-to-GDP ratio in good shape, fiscal policies and long-term restraint are crucial.